Several Applications of Solid Lipid Nanoparticles in Drug Delivery - Sulaiman Khil, Noor Hassan; Sharma, Shaweta; Sharma, Pramod K.; Alam, Aftab (Current Molecular Medicine, 2024)
Rapid progress is being made in the area of nanotechnology; solid lipid nanoparticles are currently at the forefront of research and development. They have the capability of becoming employed in an extensive number of applications, including the delivery of medications, clinical treatment, and research, in addition to uses in other areas of academic inquiry that could benefit from their utilisation. This article presents a thorough analysis of solid lipid nanoparticles, covering subjects such as their goals, preparation strategy, applications, advantages, and possible remedies for the issues that have been raised. This review provides a discussion of solid lipids that is both in-depth and comprehensive. Studies that investigate the manner in which SLNs are prepared and the routes via which they are administered are typical. Aspects concerning the route of administration of SLNs as well as the destiny of the carriers in vivo are also investigated in this paper.
Keywords: Nanotechnology